Evaluation of ponticulus posticus according to the skeletal relationship found in strict lateral radiographs - García Blásquez, Jonathan Cook (2021)
Objective: To evaluate the posticus ponticulus according to the skeletal relationship found in strict lateral radiographs at the Teaching Dental Center of the Cayetano Heredia Peruvian University during the period 2015-2017, using the classification according to the degree of mineralization described by Selby and the classification of the Steiner’s skeletal relationship. Material and Methods: It was performed on strict digital lateral radiographs using a 20-inch screen using the SIDEXIS XG program, observing the degree of mineralization of ponticulus posticus: no evidence of the bone spicule on the vertebral artery = absent bridge, when it was noted or evidenced the formation of the spicule and / or calcification in the middle of the bridge or in incomplete form = partial bridge, when the bone arch was clearly finished visualizing = full bridge and the classification of the skeletal relationship by measuring the ANB angle: Class I = 0- 4th; Class II => 4th and Class III = <0 °: the statistical analysis was done with the SPSS V.22.0 program for Windows using the Chi2 tests. Results: Of the 925 digital strict lateral radiographs evaluated, it was found that 283 radiographs presented ponticulus posticus and the highest frequency was found in the absent type (69.4%), the partial type (17.1%) and the complete type (13.5 %). Ponticulus posticus occurred in 25.1% of the female sex and in 38.4% of the male sex. The skeletal relationship associated with ponticulus posticus was presented in Class II (19.1%), Class I (10.4%) and Class III (1.1%). Conclusions: Ponticulus posticus is an anatomical variant that occurs in 30.6% of the cases. No statistically significant difference was found between the presence of ponticulus posticus and the skeletal relationship or sex.